A rare case of paediatric solitary plexiform neurofibroma of the lip. Issue 2 (March 2020) - Singh, Gautam Bir; Shukla, Indu; Aggarwal, Kiran; Malhotra, Sonali
Abstract: Solitary plexiform neurofibromatosis of the oral cavity is a sporadically reported lesion with extremely rare occurrence in lip. Here in, we present one such rare case in a six year old child and discuss its clinical relevance in view of contemporary literature on the cited subject.